2022
DOI: 10.1111/efp.12730
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological characterization of a disease associated with phytoplasmas in Andean oak, Quercus humboldtii Bonpland, in Bogotá—Colombia

Abstract: Quercus humboldtii is the dominant tree species in oak forest ecosystems in the Colombian Andes, and approximately 15,000 trees have been planted in urban Bogotá. In Bogotá, Q. humboldtii is affected by phytoplasmas. The management of phytoplasmas relies mainly on control of the insect vectors. The aim of this work was to generate information on phytoplasmas affecting Q. humboldtii and the potential insect vectors involved. Phytoplasmas were detected by nested PCR and identified by restriction fragment length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 79 publications
2
5
0
Order By: Relevance
“…Grass is the main host of these two species, so it is possible that they visit Andean oak trees occasionally when the grass is tall or the trees have low branches. Our observations suggest that these species are not the main phytoplasma vectors of Andean oaks, but they may play a marginal role in transmitting phytoplasmas to and from the grass, as has been hypothesized previously(Lamilla et al 2022). Some species of Cicadellidae and Psylloidea were collected in Andean oak trees and neighbouring plants; therefore, we propose that in addition to the movement of insect vectors from grass to trees and vice versa(Lamilla et al 2022), different species of Cicadellidae move to and from trees or shrubs dispersing phytoplasmas.…”
supporting
confidence: 68%
See 3 more Smart Citations
“…Grass is the main host of these two species, so it is possible that they visit Andean oak trees occasionally when the grass is tall or the trees have low branches. Our observations suggest that these species are not the main phytoplasma vectors of Andean oaks, but they may play a marginal role in transmitting phytoplasmas to and from the grass, as has been hypothesized previously(Lamilla et al 2022). Some species of Cicadellidae and Psylloidea were collected in Andean oak trees and neighbouring plants; therefore, we propose that in addition to the movement of insect vectors from grass to trees and vice versa(Lamilla et al 2022), different species of Cicadellidae move to and from trees or shrubs dispersing phytoplasmas.…”
supporting
confidence: 68%
“…'Candidatus Phytoplasma fraxini' (group 16SrVII) was detected in 54.6% (n = 130), 'Candidatus Phytoplasma asteris' (group 16SrI) in 30.7% (n = 73) and mixed infections of both phytoplasmas in 8.8% (n = 21) (Lamilla et al 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…), it grows well under urban conditions. Lamilla et al ( 2022 ) found an 80% prevalence of phytoplasma infection in Bogotá’s oaks, but without having lethal or severe consequences to the tree, suggesting a high level of resistance in these environments. The ECM communities associated with this species have not yet been studied in urban ecosystems.…”
Section: Introductionmentioning
confidence: 99%